Recent progress in the study of occupational lung diseases in Romania. Issue 2 (May 1975) - Barhad, B; Pilat, L; Teculescu, D
Abstract : This paper reviews studies of occupational lung diseases in Romania in the last two decades. Work concerned with the effects of exposure to textile fibres, irritant gases and fumes in the chemical industry, welding fumes, asbestos, cadmium oxide, and the relation between dust exposure, pneumoconiosis, and chronic bronchitis is briefly presented.